Selection strategy for the optimal artificial lift method (on the example of Novotroitsk field, Ukraine) - Levoniuk, S.; Taki, H. El (Національний технічний університет "Харківський політехнічний інститут", 2020)
The relevance of paper. Artificial lift is a method used to lower the producing bottomhole pressure on the formation to obtain a higher production rate from the well, adding up to the different kinds of artificial lifts with their own characteristics and restrictions, with the understanding of the importance of selecting the right artificial lift for each type of well with it is own reservoir and fluid characteristics. Currently, against the background of depletion of Ukrainian oil and gas fields, the choice of necessary method of artificial lift is very important. The purpose of article is selecting upmost efficient artificial lift system at Novotroitsk field, based on the limitations, advantages and disadvantages of each type of artificial lift system, along with reservoir characteristics and fluid phase behavior.The object of study is process of artificial lift at Novotroitsk oil-gas-condensate field. The tasks of paper is combination of methods by expert programs, technical surface and infrastructure considerations, to create an analysis to screen candidate artificial lift systems, and then to select one for implementation. The research methodology that was used is PIPESIM software with the analyzing of the different parameters including reservoir characteristics and fluid phase behavior and their effect on inflow performance relationship were investigated to study the effectiveness of the artificial lift systems.

Актуальність роботи. Штучний підйом – це метод, що застосовується для зниження вибійного тиску в свердловині, щоб отримати більш високу швидкість видобутку зі свердловини. Існують різні види штучних підйомів із власними характеристиками та обмеженнями, при цьому важливий підбір правильного штучного підйому для кожного типу свердловини з власними пластовими та флюїдними характеристиками. Наразі на тлі значного виснаження українських нафтогазових родовищ вибір правильного методу штучного підйому є дуже актуальним. Мета статті – вибір найефективнішої системи штучного підйому на Новотроїцькому родовищі на основі обмежень, переваг і недоліків кожного типу штучних підйомних систем, а також характеристик резервуара та фазового режиму. Об’єктом дослідження є процес штучного підйому на Новотроїцькому нафтогазоконденсатному родовищі. Завдання роботи полягають в поєднанні методів за експертними програмами, технічної поверхні та інфраструктурних міркувань, щоб виконати аналіз для показу систем-кандидатів штучного підйому, а потім обрати один для впровадження. Методологія досліджень – програмне забезпечення PIPESIM з аналізом різних параметрів, включаючи характеристики резервуарів та поведінку фази рідини та їх вплив на співвідношення продуктивності припливу.
Вибір стратегії для оптимального методу штучного підйому (на прикладі Новотроїцького родовища, Україна)
Keywords: production indicators; PIPESIM; oil recovery; показники видобутку; PIPESIM; вилучення нафти